1990
DOI: 10.1111/j.1469-7610.1990.tb00844.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Relationship between Specific Language Impairment, Phonological Disorders and Reading Retardation

Abstract: -Language and literacy skills were assessed in 83 8 54 -year olds whose language development had been impaired at 4 years of age. Provided that language problems had resolved by age 5 V2 years, literacy development was normal, but many of the children who still had verbal deficits at 5 V2 years of age did have reading difficulties and persisting oral language impairments later on. In these children, reading comprehension tended to be poor relative to reading accuracy. Syntactic competence in the preschool peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
633
6
81

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 898 publications
(791 citation statements)
references
References 23 publications
71
633
6
81
Order By: Relevance
“…The situation is different when SSD co‐occurs with language impairment as it frequently does: language impairment carries a strong risk of literacy difficulties affecting both word reading and reading comprehension skills. Similarly, when SSD persists to school entry when reading instruction begins, it has concurrent effects on phoneme awareness and reading skills, consistent with the critical age hypothesis (Bishop & Adams, 1990). …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The situation is different when SSD co‐occurs with language impairment as it frequently does: language impairment carries a strong risk of literacy difficulties affecting both word reading and reading comprehension skills. Similarly, when SSD persists to school entry when reading instruction begins, it has concurrent effects on phoneme awareness and reading skills, consistent with the critical age hypothesis (Bishop & Adams, 1990). …”
Section: Discussionsupporting
confidence: 74%
“…Together, our findings are broadly consistent with those reported in previous studies of speech sound disorder (Bird et al., 1995; Bishop & Adams, 1990; DeThorne et al., 2006; Lewis et al., 2000; Nathan et al., 2004). However, it is clear that the impact of speech sound disorder on literacy development is relatively short‐lived (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the semantic/syntactic factor predicted only family members' affection status for LI. Previous research has indicated that language, but not speech, skills predicts later literacy (Bishop & Adams, 1990;Catts, 1993;Magnusson & Naucler, 1990;Nathan et al, 2004). Our findings suggest that the articulation/phonology factor predicts deficits in reading in other family members within a pedigree.…”
Section: Discussionsupporting
confidence: 45%
“…Shriberg, Tomblin, and McSweeny (1998) report 11-15% co-morbidity of speech delay with LI at 6 years of age, with considerably higher co-morbidity rates estimated for preschool children with speech delay (40-60%; Shriberg & Kwiatkowski, 1994). Numerous studies have validated the utility of this dichotomy by demonstrating poorer outcomes for children with combined SSD and LI than for children with isolated SSD (Aram & Hall, 1989;Bishop & Adams, 1990;Felsenfeld, McGue, & Broen, 1995;Hall & Tomblin, 1978;Lewis, Freebairn, & Taylor, 2000;Menyuk et al, 1991;Nathan, Stackhouse, Goulandris, & Snowling, 2004;Shriberg & Austin, 1998). Young et al (2002) followed a cohort at 19 years of age that was first assessed by Stothard, Snowling, Bishop, Chipchase, and Kaplan (1998).…”
Section: Subtype Classificationsmentioning
confidence: 99%